Cases on open-linked data and semantic web applications - Ordóñez de Pablos, Patricia 1975-; Lytras, Miltiadēs 1973-; Tennyson, Robert D.; Labra Gayo, José Emilio (Information Science Reference, an imprint of IGI Global, 2013)
"This book brings together new theories, research findings and case studies that cover the recent developments and approaches toward applied open linked data and semantic web in the context of information systems" - Provided by publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung